NKX6.1 hypermethylation predicts the outcome of stage II colorectal cancer patients undergoing chemotherapy. Issue 5 (10th February 2018) - Chang, Sou‐Yi; Kuo, Chih‐Chi; Wu, Chang‐Chieh; Hsiao, Cheng‐Wen; Hu, Je‐Ming; Hsu, Chih‐Hsiung; Chou, Yu‐Ching; Shih, Yu‐Lueng; Lin, Ya‐Wen
Abstract: Colorectal cancer (CRC) is a common malignancy worldwide. CRC patients in the same stage often present with dramatically different clinical scenarios. Thus, robust prognostic biomarkers are urgently needed to guide therapies and improve treatment outcomes. The NKX6.1 gene has been identified as a hypermethylation marker in cervical cancer, functioning as a metastasis suppressor by regulating epithelial–mesenchymal transition. Here, we investigated whether hypermethylation of NKX6.1 might be a prognostic biomarker for CRC. By analyzing the methylation and expression of NKX6.1 in CRC tissues and CRC cell lines. We quantitatively examined the NKX6.1 methylation levels in 151 pairs of CRC tissues by using methylation‐specific polymerase chain reaction analysis and found that NKX6.1 was hypermethylated in 35 of 151 CRC tissues (23%). NKX6.1 gene expression was inversely correlated with the DNA methylation level in CRC cell lines in vitro. Then, we analyzed the association of NKX6.1 methylation with clinical characteristics of these CRC patients. Our data demonstrated that patients with NKX6.1 methylation presented poorer 5‐year overall survival ( P = 0.0167) and disease‐free survival ( P = 0.0083) than patients without NKX6.1 methylation after receiving adjuvant chemotherapy. Most importantly, these data revealed that stage II CRC patients with NKX6.1 methylation had poorer 5‐year disease‐free survival ( P = 0.0322) than patients without NKX6.1 methylation after adjuvant chemotherapy. Our results demonstrate that methylation of NKX6.1 is a novel prognostic biomarker in CRC and that it may be used as a predictor of the response to chemotherapy.